Rationale and Design of the Mechanistic Potential of Antihypertensives in Preclinical Alzheimer's (HEART) Trial. - Wharton, Whitney; Goldstein, Felicia C; Tansey, Malú G; Brown, Alexandra L; Tharwani, Sonum D; Verble, Danielle D; Cintron, Amarallys; Kehoe, Patrick G (J Alzheimers Dis, 2018)
Research indicates that certain antihypertensive medications alter Alzheimer's disease (AD) biomarkers in Caucasians. The renin angiotensin system (RAS) regulates blood pressure (BP) in the body and the brain and may directly influence AD biomarkers, including amyloid-β (Aβ) neuropathology, cerebral blood flow (CBF), and inflammatory markers. This hypothesis is supported by studies, including ours, showing that antihypertensives targeting the RAS reduce the risk and slow the progression of AD in Caucasians. While mounting evidence supports a protective role of RAS medications in Caucasians, this mechanism has not been explored in African Americans. To assess the mechanism by which RAS medications modify the brain RAS, cerebrospinal fluid (CSF) Aβ, CBF, and inflammatory markers in African Americans, we are conducting an eight month, Phase Ib randomized, placebo controlled trial, enrolling 60 middle-aged (45-70 years), non-demented individuals, at risk for AD by virtue of a parental history. Participants include normotensive and treated hypertensives that have never been exposed to a RAS medication. Participants are randomized (1 : 1:1) by gender and BP medication use (yes/no) to one of three groups: placebo, or 20 mg, or 40 mg telmisartan (Micardis), to determine the dose required to penetrate the CNS. Our overarching hypothesis is that, compared to placebo, both doses of telmisartan will penetrate the CNS and produce salutary, dose dependent effects on the brain RAS as well as CSF Aβ, CBF, and CSF inflammatory markers in African Americans, over eight months. This manuscript describes the trial rationale and design.
Keywords: African Americans; Aged; Alzheimer Disease; Amyloid beta-Peptides; Antihypertensive Agents; Biomarkers; Blood Pressure; Brain; Clinical Trials, Phase I as Topic; Female; Georgia; Humans; Linear Models; Male; Middle Aged; Randomized Controlled Trials as Topic; Renin-Angiotensin System; Telmisartan

A Meta-Analysis of Alzheimer's Disease Incidence and Prevalence Comparing African-Americans and Caucasians. - Steenland, Kyle; Goldstein, Felicia C; Levey, Allan; Wharton, Whitney (J Alzheimers Dis, 2016)
BACKGROUND: Several studies have shown higher Alzheimer's disease (AD) incidence rates are in African-Americans (AAs) than Caucasians (CCs). If this finding is consistent across studies, it raises important etiologic questions regarding factors responsible for this discrepancy. It also affects the likely public health burden of AD in the US in the future, as the non-Caucasian population becomes the majority. OBJECTIVE: Estimate the AA/CC rate ratio for AD incidence across all available studies. METHODS: We conducted a meta-analysis of population-based studies for the rate ratio (RR) of AD incidence for AAs versus CCs, after identifying six relevant studies from the literature. We calculated an AA/CC rate ratio across all studies using inverse-variance weighting, and assessed inter-study heterogeneity. Using these incidence data, as well as data on survival after diagnosis, and on all-cause mortality, we also estimated the US prevalence of AD among AAs and CCs. RESULTS: There were six population-based studies with data comparing AD incidence between AAs and CCs, with an estimated 370 AA and 640 CC incident cases. The meta-analysis RR showed that the AD rate for AAs was 64% higher than for CCs (RR = 1.64 (95% CI 1.35-2.00)) 1.35-2.00)), with no evidence of heterogeneity. We estimated the current US AD prevalence for ages 65-90 to be 5.5% for CCs, and 8.6% for AAs (prevalence ratio 1.56). CONCLUSION: AAs have an increased risk of incident and prevalent AD compared to CCs for reasons which are unknown, but are hypothesized to reflect biological, psychological, and socioeconomic factors.
Keywords: African Americans; Alzheimer Disease; Community Health Planning; European Continental Ancestry Group; Female; Follow-Up Studies; Humans; Incidence; Male; Prevalence